2015
DOI: 10.1089/thy.2015.0130
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Papillary Thyroid Cancer Increases the Risk of Central Lymph Node Metastasis

Abstract: There is a significant association between multifocal PTC and level VI lymph node positivity, increasing proportionally with the number of foci. These findings recognize multifocality as a sign of tumor aggressiveness, as evidenced by a higher propensity for lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 30 publications
(16 reference statements)
7
67
2
1
Order By: Relevance
“…It is important to consider multifocality when deciding on the extent of surgical therapy, because it is a sign of tumor aggressiveness and is associated with an increased risk of lymph node metastasis and recurrent disease. 11,[33][34][35] This is also found in our series, where 42% (n 5 5) of the patients with a multifocal tumor had tumor invasion outside the thyroid.…”
Section: Histopathological Characteristicssupporting
confidence: 83%
“…It is important to consider multifocality when deciding on the extent of surgical therapy, because it is a sign of tumor aggressiveness and is associated with an increased risk of lymph node metastasis and recurrent disease. 11,[33][34][35] This is also found in our series, where 42% (n 5 5) of the patients with a multifocal tumor had tumor invasion outside the thyroid.…”
Section: Histopathological Characteristicssupporting
confidence: 83%
“…The role of multifocality as a risk factor for a more severe clinical course is controversial. However, several reports have suggested multifocality status as a poor prognostic factor (38,39). In the present analysis of individual SNPs, only one variant (rs2439302) displayed significant association with multifocality.…”
Section: Discussioncontrasting
confidence: 49%
“…In this study, the incidence of BRAF V600E mutation was 50.6%, which was consistent with those in other studies. In terms of multifocality, it was considered as an independent factor for CLNM [15]. For this study, we compared clinicopathological factors in the patients with and without CLNM through univariate and multivariate analysis firstly.…”
Section: Discussionmentioning
confidence: 99%
“…Multifocality also frequently exhibits in PTC. Certain studies have indicated that multifocal carcinoma in PTC is positively associated with the incidence of CLNM [14,15], while other studies have argued that there is no association between multifocality and CLNM [16]. In addition, multifocality has found to significantly increase the incidence of recurrence [17].…”
mentioning
confidence: 99%